2000
DOI: 10.1007/s002320001021
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of the Plasma Membrane Calcium Pump. Quantitative Analysis of Its Dependence on Lipid-Protein Interactions

Abstract: Thermal stability of plasma membrane Ca(2+) pump was systematically studied in three micellar systems of different composition, and related with the interactions amphiphile-protein measured by fluorescence resonance energy transfer. Thermal denaturation was characterized as an irreversible process that is well described by a first order kinetic with an activation energy of 222 +/- 12 kJ/mol in the range 33-45 degrees C. Upon increasing the mole fraction of phospholipid in the mixed micelles where the Ca(2+) pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 30 publications
4
46
0
Order By: Relevance
“…In addition, this limit value was similar to that obtained for the membrane protein reconstituted in liposomes with the same lipid composition (Levi et al 2000), but lower than that measured for the enzyme in the native membrane. The value characterizing maximal stability (k min ) was found to be dependent on the type of phospholipids included in the mixed micelles, and was also affected when phospholipids undergo chemical modifications, such as nonenzymatic glycation of phosphatidylethanolamine, a common alteration in uncontrolled diabetes mellitus (Levi et al 2008).…”
Section: Modulating the Kinetic Stability Of Membrane Proteins By Phosupporting
confidence: 81%
See 4 more Smart Citations
“…In addition, this limit value was similar to that obtained for the membrane protein reconstituted in liposomes with the same lipid composition (Levi et al 2000), but lower than that measured for the enzyme in the native membrane. The value characterizing maximal stability (k min ) was found to be dependent on the type of phospholipids included in the mixed micelles, and was also affected when phospholipids undergo chemical modifications, such as nonenzymatic glycation of phosphatidylethanolamine, a common alteration in uncontrolled diabetes mellitus (Levi et al 2008).…”
Section: Modulating the Kinetic Stability Of Membrane Proteins By Phosupporting
confidence: 81%
“…The influence of the relative concentration of phospholipid and detergent on the thermal stability of membrane proteins can be studied using two alternative experimental designs: either the concentration of detergent is kept constant while the amount of added phospholipids is increased, or vice versa. Comparison between these kinds of experiments performed using the plasma membrane calcium pump as a model, showed that similar values of k app were obtained when the mole fractions of the phospholipids in the micelles were similar, even if the phospholipid concentrations in the whole system were different (Levi et al 2000). This indicates that the effect of phospholipids and detergent on membrane protein stability is related to the micellar phase composition but not to the concentration of micelles in the system.…”
Section: Modulating the Kinetic Stability Of Membrane Proteins By Phomentioning
confidence: 83%
See 3 more Smart Citations